Dérivation nominale et innovations dans les langues indo‑européennes anciennes - Blanc, Alain; Boehm, Isabelle (Littérature & Linguistique, 2021)
The thirteen papers brought together in this volume are devoted to the phenomenon of derivation from Indo-European (Vedic Sanskrit, Tokharian, Old Norse, Old Slavic, Ancient Greek, Latin) up to our modern languages. The contributions gathered here offer, for a part of them, new hypotheses on the origin of certain suffixes, while others expose the results of their evolutions and their productivity. Synchronic and diachronic observations on suffixal behavior concern semantics, the question of the development of specialized vocabulary and that of their strictly grammatical role, in particular the relationship between adjective and substantive. A contribution focused on the accent concludes the volume.